ANTIOXIDANT ACTIVITY EVALUATION OF CATFISH (CLARIAS SP.) COLLAGEN EXTRACT USING DPPH AND ABTS METHODS - Faramita Hiola; Wiwit Zuriati Uno; Mahdalena Sy. Pakaya; Ariani Hutuba (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aimed to evaluate the antioxidant activity of collagen extracted from catfish (Clarias sp.) using DPPH and ABTS assays. The research procedures included sample preparation, collagen extraction using an acid-based method, and antioxidant analysis at concentrations ranging from 20–100 ppm. The degree of hydrolysis (DH) was measured to determine the effectiveness of Alkalase in producing bioactive peptides. The results showed that higher enzyme concentrations led to increased DH, with the highest value of 62.42% obtained at 3% Alkalase. Antioxidant activity increased with sample concentration, with maximum inhibition values of 78.57% (DPPH) and 85.00% (ABTS) at 100 ppm. The ABTS assay exhibited higher sensitivity than DPPH. These findings indicate that catfish collagen has strong potential as a safe and natural antioxidant source suitable for further development in food, pharmaceutical, and cosmetic applications.